Principles of enzymology for the food sciences - Whitaker, John R. (Marcel Dekker, 1994)
Completely revised and updated throughout, this Second Edition of a standard reference/​text explains the fundamentals of enzymology and describes the role of enzymes in the food, agricultural, and health sciences. Maintaining those features that sent the previous edition into multiple printings, Principles of Enzymology for the Food Sciences, Second Edition provides new methods for protein determination and purification . . . examines the novel concept of hysteresis . . . furnishes new information on proteases, oxidases, polyphenol oxidases, lipoxygenases, and the enzymology of biotechnology . . . details current knowledge of starch, glycogen, and cellulose degrading enzymes . . . shows how and why experimental and environmental parameters influence enzyme activity . . . discusses the effect of enzyme concentration, substrate concentration, pH, temperature, inhibitors, and activators on enzyme activity . . . describes the active site and factors that account for enzyme activity . . . delineates hydrolytic and oxidative enzymes of major importance . . . and much more.